INFLUENCE OF THE CHARACTERISTICS OF THE TRANSFORMATION OF THE CHANNEL FLOW TO A MAXIMUM RESIDUAL VELECHINY TOTAL WASHOUT - Bashkevich, I. V. (Science and Transport Progress, 2010)
In the article the theoretical research of influence of transformation features of river-bed expense on the maximal and remaining value of general washout is presented. In the mathematical model of general washout the transformation feature of river-bed expense is written down with the generalized power. In this context, an issue about the necessity of improvement of method for analytical determination of the remaining washout in the system of long-term forecast of washout on bridge transitions appears.